2020
DOI: 10.3389/fendo.2020.615082
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Patients With Pancreatic Neuroendocrine Neoplasms

Abstract: ObjectiveDiabetes mellitus (DM) is probably a risk factor for pancreatic neuroendocrine neoplasms (PNENs). However, the prevalence of DM in PNEN patients remains inconclusive. In the present study we observed the prevalence of DM and possible risk factors in PNEN patients.MethodsAfter excluding those with insulinoma, a total of 197 patients with PNENs were included. The demographic data, pathological characteristics, and data of blood biochemical tests were recorded. DM was considered if there was evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Both were higher than the overall prevalence of DM among adult Chinese individuals (35.7% and 10.9%, respectively) ( 18 ). When both fasting plasma glucose (FPG) and 2-hour postprandial plasma glucose were used to detect dysglycemia, the prevalence of NOD in PBLMT patients was comparable to that in PNET patients (9.4%) and IPMN patients (6%) in the previous studies ( 10 , 11 ). However, the prevalence of pre-DM in our study was more than seven times higher than that previously found in PNET patients (7.1%), which was assessed by preoperative FPG measurement only ( 10 ).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Both were higher than the overall prevalence of DM among adult Chinese individuals (35.7% and 10.9%, respectively) ( 18 ). When both fasting plasma glucose (FPG) and 2-hour postprandial plasma glucose were used to detect dysglycemia, the prevalence of NOD in PBLMT patients was comparable to that in PNET patients (9.4%) and IPMN patients (6%) in the previous studies ( 10 , 11 ). However, the prevalence of pre-DM in our study was more than seven times higher than that previously found in PNET patients (7.1%), which was assessed by preoperative FPG measurement only ( 10 ).…”
Section: Discussionmentioning
confidence: 58%
“…When both fasting plasma glucose (FPG) and 2-hour postprandial plasma glucose were used to detect dysglycemia, the prevalence of NOD in PBLMT patients was comparable to that in PNET patients (9.4%) andIPMN patients (6%) in the previous studies (10,11). However, the prevalence of pre-DM in our study was more than seven times higher than that previously found in PNET patients (7.1%), which was assessed by preoperative FPG measurement only (10). Indeed, more patients with prediabetes could be ignored by FPG alonethanbycombinedOGTT (19,20).Therefore,wethinkourstudy may reflect the actual dysglycemia status of PBLMT patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The results obtained with our Atrx models interestingly suggest the potential role of ATRX in the homeostasis of human pancreatic endocrine function. T2D is a significant risk factor for PanNET development [65,66], but these patients are also at risk for T2D development [67,68]. An association between metabolic syndrome and GEP-NET patients has also been found [69].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding secondary malignancies, a retrospective study of USA SEER database on GEP-NEN found an occurrence of second cancers in 25.8%, though this risk was only associated with gastro-intestinal NEN ( Kauffmann et al 2014 ). One study reported an association between metabolic syndrome and well-differentiated GEP-NEN, and others reported diabetes mellitus as a possible risk factor for the development of Pan-NEN ( Haugvik et al 2015 , Leoncini et al 2016 , Santos et al 2018 , Zhuge et al 2020 ). Concerning functioning tumors known to be associated with hyperglycemia, we only have five cases – three glucagonoma and two ACTHoma-related Cushing’s syndrome.…”
Section: Discussionmentioning
confidence: 99%